Pembuatan Antarmuka Sistem Pemantau Ruangan Berbasis Web - Ruli Handrio; R. Rizal Isnanto; Eko Didik Widianto (Department of Computer Engineering, Engineering Faculty, Universitas Diponegoro, 2016)
As the advancement of technology, there are a lot of things that could be efficiently done by technology. Technology of surveillance system is necessary and highly demanded by many people at the current moment. The interface of room surveillance system using PHP programming language and MySQL as a database management system which can generate video and other information as an output in a web-based browser. The result of this research is an interface of surveillance systems that can be used as room monitoring. The result of the Black box testing from this interface of surveillance system indicates that all of the system function has been successfully operated. Hopefully, this research can be used to help for further research.